Kepadatan Populasi, Struktur Ukuran, Hubungan Panjang–Berat, dan Pola Sebaran Bia Jala (Strombus luhuanus) di Pantai Asol, Pulau Haruku - Rikhe Fransy Kaihatu; Handy Erwin Pier Leimena; La Eddy (Pusat riset dan Inovasi Nasional, 2025)
This study evaluated the population status of the conch Strombus luhuanus at Asol Beach, , Haruku Island, Maluku, through an analysis of density, size structure, length–weight relationship, and spatial distribution. Data were collected using transect–quadrat methods in the intertidal zone during low tide, complemented by measurements of environmental parameters (temperature, salinity, pH, and dissolved oxygen). The results revealed a population density of 2.76 ind/m², classified as moderate compared to other sites in Maluku. Shell length distribution encompassed nine size classes, with dominance in the mid-size class (3.93–4.38 cm), indicating successful recruitment of juveniles to early adults. The length–weight relationship followed the equation W = 1.871L0.0521 (R² = 0.857) with a negative allometric growth pattern, suggesting that individuals allocate more energy to shell elongation than body mass increase. The Morisita index (Id = 211.07) indicated an aggregated distribution pattern, consistent with reproductive strategies of broadcast-spawning gastropods. Environmental conditions (temperature 28.7 °C; salinity 32.66‰; pH 6.44; DO 6 mg/L) were within the tolerance range of tropical intertidal mollusks. These findings highlight the critical role of sandy seagrass habitats in supporting S. luhuanus populations and emphasize the need for management strategies based on minimum catch size, harvest regulation, and coastal habitat protection.